Desenvolvimento de um dispositivo para obtenção de monocristais de ligas à base de cobre - Blanco, Matildes [UNESP]; Barelli, Nilso [UNESP]; Vicente Benedetti, Assis [UNESP]; Andrade Flor, Samuel Waldemar (FapUNIFESP (SciELO), 2003)
This paper describes the drawing, construction and optimization of a device, which can be used to obtain single crystals of different metallic materials with melting point from 550 to 1050°C. Components of ease obtaining and of low cost were used. The device was based on the modified Bridgman technique and it was used to obtain single crystals of copper-based alloys. The temperature axial profiles and a difference less then 1% in the temperature between the wall and the center of the ceramic tube in the critical region for obtaining single crystals of good quality indicated that the oven presents a good thermal stability. Single crystals of CuZnAl and CuAlAg alloys of good quality were growth and characterized using optical microscopy and Laüe X-ray back reflection.
Development of a device for obtaining single crystals of copper-based alloys
Keywords: Copper-based alloys; Modified Bridgman technique; Single crystal; alloy; aluminum derivative; copper complex; silver derivative; zinc derivative; cost benefit analysis; crystal structure; device; extraction; high temperature; melting point; quality control; technique; temperature dependence; thermostability; X ray crystallography